2017
DOI: 10.1159/000486409
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation with the Slim Modiolar Electrode Nucleus CI532® Cochlear Implant: A Preliminary Experience

Abstract: As the indications for cochlear implant have expanded to include younger patients and individuals with greater degrees of residual hearing, increasing emphasis has been placed on atraumatic surgery and the preservation of the cochlear structure. Here, a descriptive prospective randomized study was performed. It was shown that residual hearing preservation is possible 12 months postoperatively with an atraumatic perimodiolar flexible electrode array CI532® (Cochlear Ltd, Sydney, Australia). Residual hearing pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…We chose to present our data according to the most common definitions used in the literature. The hearing preservation rates achieved with the SME appear to be superior to other stylet-type PMEs [21,42,43]. The majority of patients (72%) were initially fitted with an EAS strategy and 44% experienced benefits with the acoustic stimulation and continued to use the device.…”
Section: Discussionmentioning
confidence: 89%
“…We chose to present our data according to the most common definitions used in the literature. The hearing preservation rates achieved with the SME appear to be superior to other stylet-type PMEs [21,42,43]. The majority of patients (72%) were initially fitted with an EAS strategy and 44% experienced benefits with the acoustic stimulation and continued to use the device.…”
Section: Discussionmentioning
confidence: 89%
“…In 63.6% of the participants without a tip fold-over (n = 22), all electrode contacts were placed inside the ST, whereas 36.4% showed a translocation from the ST to the SV. In comparison, Shaul et al [11], Aschendorff et al [12] and Ramos et al [16] found that 100% of in total 73 participants had full ST placement of the SPE; a CS approach was used in 15 participants, and the eRW or RW approach in 58 participants. While evaluating scalar location in 23/117 participants, McJunkin et al [15] found 73.9% to have full ST insertion all implanted using the eRW approach.…”
Section: Scalar Positionmentioning
confidence: 99%
“…It was observed that independent of the type of electrode used, full scala tympani (ST) position [8] and preservation of residual hearing [8,10] is more likely using a RW or eRW approach, compared to the CS approach. These findings might contribute to the fact that to-date, eRW and RW approaches were used in 91.8% (236/257) of the participants in the five studies that investigated the SPE [11,12,[14][15][16].…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations